Preparation of Aniline Dimer-COOH Modified Magnetite (Fe3O4) Nanoparticles by Ultrasonic Dispersion Method - Taka, Zakiyyu Ibrahim; Mustafa, Mohd Kamarulzaki; Asman, Saliza; Sekak, Khairunnadim Ahmad; Muhammada, Jibrin (International Journal of Engineering and Technology, 2018)
The magnetite (Fe3O4) nanoparticles capped with certain level of aniline dimer-COOH were prepared via assisted ultrasonic dispersion method and characterized by X-ray Diffraction spectra (XRD), Field Emission Scanning Electron Microscope (FESEM), Ultraviolent UV-visible (UV-vis) and Fourier Transformation Infrared spectroscopy (FTIR). The XRD result shows that both the sample of Fe3O4 nanoparticles synthesized without aniline dimer-COOH have similar peaks with the one that were capped with aniline dimer-COOH, this indicated the higher purity crystalline peaks of Fe3O4 nanoparticles was successfully synthesized. The Field Emission Scanning Electron Microscope (FESEM) result shows that, the aniline dimer-COOH modified magnetite nanoparticles are less agglomerated with spherical shape and continues size distribution, and the obtained image from EDS indicates the present of Fe3O4 nanoparticles by showing Fe-O group of element. The magnetic properties of the magnetite nanoparticles prepared by ultrasonic irradiation method was observed by vibrating sample magnetometer (VSM), the hysteresis loop of Fe3O4 nanoparticles observed by VSM has a saturation magnetization at 89.46 emug-1 indicating super paramagnetic behavior of the Fe3O4 nanoparticles.Â Â